Syntheses and reactions of aminooxycarbenes from thermolysis of Δ³-1,3,4-oxadiazolines - Couture, Philippe (My University, 1997)
Δ³-1,3,4-Oxadiazolines, spiro-fused at C2 to C2 to oxazolidines (33a,b) or to C2 of tetrahydro-1,3-oxazines (106a-c), were synthesized by oxidation of semicarbazones 103 with PhI(OAc)₂. Oxadiazoline 33a was reacted with acylating agents and with benzenesulfonyl chloride to give 33c-j and 33k, respectively. Oxadiazolines 106d and 106e were prepared by reacting 106a and 106b, respectively, with benzoyl chloride. Thermolysis of oxadiazolines 33 and 106 in benzene at 90⁰C (k⁹⁰∼1-50x10⁻⁵s⁻¹) generated oxazolidin-2-ylidenes 28 and tetrahydro-1,3-oxazin-2-ylidenes 113, respectively, as major fragmentation intermediates. Specifically, 33c-j and 106d,e (N-carbonyl) gave essentially quantitative yields of the corresponding aminooxycarbenes, while thermolysis of 3b (N-methyl) produced ca. 70% of 28b; for 106c (N-methyl), an upper limit of ca. 20% was determined for the formation of 113c. Experiments on the thermolysis of 2,2-dioxy oxadiazolines 86 at 110⁰C in benzene led to the detection (and isolation, in one case) of ketene acetals 87 as minor products; compounds tentatively identified as oxiranes 94 were also observed. Formation of these and other products was rationalized in terms of a thermolytic scheme involving the intermediacy of carbonyl ylides 91 which predominantly fragment to dioxycarbenes 92 and acetone. Aminooxycarbenes 28b-g,j and 113d,e were intercepted with phenols to give OH insertion products 119/124; an activation energy of 20.4 kcal/mol was measured for nitrogen inversion in oxazolidines 119. Carbenes 28b,d-f and 113d reacted with two equivalents of methyl or phenyl isocyanate to give hydantoins 120; in contrast, 4(5H)-oxazolones 125 formed when 28d,f or dimethoxycarbene () were generated in the presence of benzoyl isocyanate. The major products in the reaction of 28d-f with dimethyl acetylenedicarboxylate or with methyl propiolate, oxazolines 157, resulted from apparent acyl transfers from N to C in the proposed dipolar intermediates. Carbene 28f inserted into the activated CH bond of 1,3-diones to produce 170; the minor products of these reactions (e.g. 173) provided evidence for the involvement of ion pairs. β-Lactam-4-ylidene 194, generated from thermolysis of β-lactam oxadiazoline 193, underwent intramolecular OH insertion to give 2,3-benzooxapenam 195 in 53% yield.
Keywords: Chemistry; Chemistry